Normative intersections and the poetics of hybridity in Cratinus’ Chiron (Circe de clásicos y modernos, 2019)
Starting from a study on the category of hybridity, this paper examines the extant fragments of Cratinus’ Chirons, whose isolated testimonies include several didactic verses in which the distinction between nature and civilization becomes disrupted with a clear humorous intention. Within an environment of mixture and heterogeneity, the play manages to create a distorted reflection of reality in which men, animals and gods coexist without rules in a world saturated by political, legal, sexual and lexical corruption. Through an overlapping of the figure of Cratinus and the chorus of Centaurs, these political subversions prove not to be alien to the procedures frequently installed by the comic genre when crossing borders and playing with intertexts. The play then produces interesting effects by mixing and intersecting opposites and exploiting the hybrid nature of its wide variety of allusions.
Keywords: Cratinus; Chirons; hybridity; Old Comedy; normativity